LEADERSHIP AND MOTIVATION TO PERFORMANCE EMPLOYEE IN PAPUA PROVINCE - Ferdinandus Christian (Salewangang Institut Publishing, 2018)
This study aims to determine the influence of leadership and motivation on the performance of employees at the Food Security and Coordination Counseling of Papua Province. Respondents in this study as many as 84 employees at the Office of Food Security and Coordination Counseling of Papua Province and respondents who returned questionnaires of 60 questionnaires, Data processed using Multiple Regression and using SPSS software version 20. The result of this research shows that leadership has significant effect on employee performance while work motivation has significant effect on employee performance. The result of simultaneous research shows that leadership (X1) and work motivation (X2) have significant effect on employee performance.